Book Reviews (The Muslim world, 1984)
Book reviewed in this article: Islam: A Survey of the Muslim Faith. By C. George Fry and James R. King. Islam and the West: The Moriscos. A Cultural and Social History. By Anwar G. Chejne. The Muslim Community in North America. Edited by Earle H. Waugh, Baha Abu-Laban, and Regula B. Qureshi. Islam in India: Studies and Commentaries. Edited by Christian W. Troll. The Afghan Connection: The Extraordinary Adventures of Major Eldred Pottinger. By George Pottinger. Modern Arab Thought: Channels of the French Revolution to the Arab East. By Ra'?f Khūr?, translated by Iḣsān 'Abbās, edited by Charles Issawi. The Palestinian Liberation Organisation: People, Power and Politics. By Helena Cobban. The Zionist Connection II: What Price Peace? By Alfred M. Lilienthal. Faith and Power: The Politics of Islam. By Edward Mortimer. Sex and Society in Islam: Birth Control Before the Nineteenth Century. By B. F. Musallam. Studies on Byzantium, Seljuks, and Ottomans: Reprinted Studies. Byzantina kai Metabyzantina, Vol. 2. By Speros Vryonis, Jr. Malibu Society and Religion in Early Ottoman Egypt: Studies in the Writings of 'Abd al-Wahhab al-Sha'ran?. By Michael Winter. Chants Musulmans en Peul. By J. Haafkens. Love, Madness, and Poetry: An Interpretation of the Maǧnūn Legend. By As'ad E. Khairallah. The Churches and Islam in Europe (II). By Jan Slomp and others. The Republic of Lebanon: Nation in Jeopardy. By David C. Gordon. I Speak for Lebanon. Kamal Joumblatt. Translated by Michael Pallis. Issues in Islamic Banking: Selected Papers. By Muhammad Nejatullah Siddiqi. The Memoirs of a Syrian Prince: Abu'l-Fidā', Sultan of Hamāh (672–732/1273–1331). Translated with an introduction by P. M. Holt. Une Herméneutique de la Tradition Islamique: Le Commentaire des Arba'ūn al-Nawaw?ya de Muḣy? al-D?n Yaḣy? al-Nawaw? (m. 676/1277): Introduction, texte arabe, traduction, notes et index du vocabulaire. By Louis Pouzet.